Historic Amenities and Housing Externalities: Evidence from The Netherlands - Hans R.A. Koster; Jan Rouwendal (Tinbergen Institute, 2015)
It has been argued that the growth of cities is increasingly determined by the presence of amenities. We study the economic effects of large scale subsidised investments in historic amenities, by looking at their impact on house prices. We aim to distinguish between the direct and indirect effect of investments. The latter implies a change in the behaviour of neighbours via changes in the level of maintenance of the house. We use a large nationwide dataset with housing transactions from 1985-2011 and data on investments in cultural heritage. To control for the fact that these investments are non-randomly distributed over space we use repeat sales. Furthermore, we construct an instrument based on yearly fluctuations in the size of national subsidy programmes to maintain cultural heritage. We show that a one million euro per square kilometre increase in investments in cultural heritage leads to a price increase of 1.5-3.0 percent of non-targeted buildings. We do not find evidence that the maintenance state of properties that are not eligible for subsidies are improved, suggesting that any price effect due to investments in cultural heritage is a direct effect of investments.
Keywords: R30; R33; 330; cultural heritage; historic amenities; housing externalities; hedonic pricing